Aggregate Supply and Supply-Side Intervention. - Gregory, M (International Thomson Business Press, 1996)
M. Mackintosh, V. Brown, N. Costello, G. Dawson, G. Thompson and A. Trigg (eds.), Economics and Changing Economies, International Thomson Business Press for The Open University, 1996, pp. 592-627.